2009
DOI: 10.1051/cocv/2009002
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuity theorem in the micropolar elasticity

Abstract: Abstract. In this paper we investigate the equivalence of the sequential weak lower semicontinuity of the total energy functional and the quasiconvexity of the stored energy function of the nonlinear micropolar elasticity. Based on techniques of Acerbi and Fusco [Arch. Rational Mech. Anal. 86 (1984)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…From (38)- (40), the constants U k , F k , and W k can be obtained. The stress components can be evaluated by substituting (36) into (15) and (18), and then into (19).…”
Section: Third-order Shear Deformation Theory (Tsdt)mentioning
confidence: 99%
See 4 more Smart Citations
“…From (38)- (40), the constants U k , F k , and W k can be obtained. The stress components can be evaluated by substituting (36) into (15) and (18), and then into (19).…”
Section: Third-order Shear Deformation Theory (Tsdt)mentioning
confidence: 99%
“…By comparing (30) and (40), it is found that e à ij j ð Þ in (40) denote the densities in j-space of the amplitude. From (40), the displacements due to the eigenstrains may be expressed as…”
Section: Arbitrary Distributionmentioning
confidence: 99%
See 3 more Smart Citations